The Role of B Cells in Scleroderma Lung Disease Pathogenesis - Liossis, Stamatis-Nick C.; Staveri, Chrysanthi (Frontiers in Medicine, 2022)
Systemic sclerosis (SSc) is a chronic, autoimmune, multisystem disease characterized by tissue fibrosis that, apart from the skin, may affect the lungs among other organs. B cells have been found in tissue lymphocytic infiltrates; in the lungs are encountered in lymphoid aggregates. The abnormal and hyperreactive B cell in SSc may initiate and perpetuate the fibrotic process via incompletely understood mechanisms. Studies in animal models of SSc have demonstrated that B cell dysregulation is an early event in disease pathogenesis. Functional disturbances of BCR signaling such as decreased inhibitory CD22 signal transduction or augmented CD19-mediated signaling result in prolonged B cell activation. Antagonism of BAFF, a cytokine known for his central role in B cell survival and maturation, not only suppresses the production of fibrogenic cytokines such as IL-6 and IL-10, but also amplifies antifibrogenic cytokine secretion such as IFN-γ and it finally contributes to skin fibrosis attenuation. B cells subsets in SSc patients display several abnormalities. Naïve B cells are increased, in contrast to switched memory B cells that are not only decreased but also activated. Disturbances in the expression of molecules that are involved in B cell tuning have also been described. Interestingly, a distinct B cell population characterized by anergy and exhaustion has been found to be increased in patients with SSc-ILD. Another B cell subset, the CD30+GM-Beff, is capable to differentiate monocytes to dendritic cells and is increased in SSc patients with ILD. Of note, patients with SSc-ILD exhibit increased expression of the inhibitory receptor FcγRIIB on naïve and double negative B cells aiming perhaps to counterbalance the abnormal B cell activation. Studies of B cell targeted treatments have demonstrated promising clinical efficacy. Therefore, B cell eliminating therapies could be integrated into the therapeutic armamentarium of patients suffering from SSc-ILD aiming to at least stabilize the fibrotic lung process.